Is soil management system really important? comparison of microbial community diversity and structure in soils managed under organic and conventional regimes with some view on soil properties. - Kamila Rachwał (Public Library of Science (PLoS), 2021)
The fertility and productive value of soil are closely related to the physical and chemical properties of the soil as well as its biological activity. This activity is related to the intensity of microbially catalysed processes of transformation of organic and mineral substances contained in the soil. These processes are closely correlated with the abundance and biodiversity of soil microorganisms, especially bacteria, and the activity of enzymes produced by them. In this article we have compared some physicochemical properties of soil derived from conventional and organic farms and microbial communities inhabiting these ecosystems. We aim to investigate whether the soil management regime affects the abundance and diversity of these environments in terms of bacteria. Some differences in microbial communities were observed, but the rhizosphere of plants from organic and conventional soils does not harbour separate microbiomes. Albeit, the method of fertilization influences the diversity of soil microorganisms. A greater diversity of bacteria was observed in soils from farms where organic fertilizers were applied. Soil pH and activity of some soil enzymes were also shown to differ between organic and conventional soil cropping systems.